1997
DOI: 10.1038/43160
|View full text |Cite
|
Sign up to set email alerts
|

A new route for synthesis of dimethylsulphoniopropionate in marine algae

Abstract: The 3-dimethylsulphoniopropionate (DMSP) produced by marine algae is the main biogenic precursor of atmospheric dimethylsulphide (DMS). This biogenic DMS, formed by bacterial and algal degradation of DMSP, contributes about 1.5 x 10(13) g of sulphur to the atmosphere annually, and plays a major part in the global sulphur cycle, in cloud formation and potentially in climate regulation. Although DMSP biosynthesis has been partially elucidated in a higher plant, nothing is known about how algae make DMSP except t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
165
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 27 publications
8
165
2
Order By: Relevance
“…Keller et al (1999) also found that DMSP increased in T. pseudonana under nitrogen-limited conditions, while the nitrogenous osmolytes, including Gly betaine and amino acids, were depleted. The proteins involved in the DMSP biosynthesis pathway have yet to be identified, although it is thought that the first step involves the transamination of Met, to yield the 2-oxo acid 4-methylthio-2-oxobutyrate (Gage et al, 1997). As discussed above, we identified a branched-chain aminotransferase (ProtID 260934) as the most highly increased protein at the onset of nitrogen starvation, and this may be a candidate for the enzyme catalyzing this step.…”
Section: Protein and Amino Acid Metabolismmentioning
confidence: 90%
“…Keller et al (1999) also found that DMSP increased in T. pseudonana under nitrogen-limited conditions, while the nitrogenous osmolytes, including Gly betaine and amino acids, were depleted. The proteins involved in the DMSP biosynthesis pathway have yet to be identified, although it is thought that the first step involves the transamination of Met, to yield the 2-oxo acid 4-methylthio-2-oxobutyrate (Gage et al, 1997). As discussed above, we identified a branched-chain aminotransferase (ProtID 260934) as the most highly increased protein at the onset of nitrogen starvation, and this may be a candidate for the enzyme catalyzing this step.…”
Section: Protein and Amino Acid Metabolismmentioning
confidence: 90%
“…conversion of Met to DMSP based on radiolabeling metabolite studies (Gage et al, 1997;Summers et al, 1998) would be elevated in association with salinityinduced DMSP elevation. Eighteen of the 36 proteins increased under high-salinity/DMSP conditions classified within the four enzyme classes in the proposed Met-DMSP synthesis pathway (Fig.…”
Section: Candidate Dmsp Synthesis Enzymesmentioning
confidence: 99%
“…Microalgae, such as sea-ice diatoms, are believed to utilize an alternative Met transaminase pathway. Radiolabeling studies of pathway metabolites showed algal DMSP synthesis sequentially utilizes 2-oxoglutarate-dependent aminotransferase, NADPH-linked reductase, S-adenosyl Met (SAM)-dependent methyltransferase (SAMmt), and oxidative decarboxylase (Gage et al, 1997;Summers et al, 1998). Analyzed most extensively in the green macroalgae, Ulva intestinalis, radiolabeled metabolites also supports presence of this pathway in haptophyte, diatom, and prasinophyte species.…”
mentioning
confidence: 99%
See 2 more Smart Citations